3-D X-ray computed tomography on failure characteristics of rock-like materials under coupled hydro-mechanical loading. (December 2019) - Kou, Miaomiao; Liu, Xinrong; Tang, Shangding; Wang, Yunteng
Highlights: Influence of internal fluid pressures on fracture behavior in rock-like materials is experimentally studied. 3-D X-ray computed tomography combined with 3-D reconstruction technique is employed to investigate the internal failure characteristics. Fractal dimensional analysis of 3-D failure fragments under the coupled hydro-mechanical loading conditions is conducted. Scanning Electron Microscope (SEM) technique reveals fracture surface roughness in the regions of crack initiation at the microscopic scale. Abstract: In this article, influences of confining pressures and internal fluid pressures on fracture behavior in rock-like materials subjected to both mechanical loads and internal hydraulic pressures is experimentally studied using the 3-D X-ray computed tomography combined with 3-D reconstruction techniques. Six different types of the pre-cracked rock-like specimens subjected to different confining pressures and internal fluid pressures are first conducted using a rock mechanics testing system. Then, the broken pre-flawed rock-like specimens are analyzed using a 3-D X-ray computed tomography (CT) scanning system. Subsequently, the internal damage behavior of failed pre-flawed rock-like specimens is evaluated by the 3-D reconstruction techniques, according to the horizontal and vertical cross-sectional CT images. The experimental results demonstrate that the peak strengths of pre-cracked rock-like specimens in the triaxial compression with fixed confining pressures decrease as the internal fluid pressures increases. On the other hand, when the internal fluid pressures are fixed, peak strengths of pre-cracked rock-like specimens in the triaxial compression increase with increasing the confining pressures. Furthermore, the 3-D X-ray Computed Tomography technique provides that the ultimate 3-D internal failure mode in pre-cracked rock-like specimens under the hydro-mechanical loading conditions are affected by both confining pressures and internal fluid pressures. Influences of confining and internal fluid pressures on the crack areas, crack aperture extent and the fractal dimension of 3-D fragments are investigated to reveal the coupled hydro-mechanical fracturing mechanism. In addition, the Scanning Electron Microscope (SEM) observations illustrate that the fracture surface roughness in the regions of crack initiation at the microscale decreases as the internal fluid pressures increases.